THE INFLUENCE OF STRATEGIC HUMAN RESOURCE MANAGEMENT (SHRM) ON EMPLOYEE JOB SATISFACTION AT THE CLASS IIA CORRECTIONAL FACILITY IN YOGYAKARTA - Laila Rahmawati Pratama; Kusmiyanti Kusmiyanti (Journal of Management Small and Medium Enterprises (SME's))
The purpose of conducting this research was to determine the influence of Strategic Human Resource Management on employee job satisfaction in Lembaga Pemasyarakatan Kelas IIA Yogyakarta. This study used a quantitative method with a non-probability sample technique of 123 employees. Data collection techniques were carried out using questionnaires which were distributed through the Google Form. There are 40 statements used indicators in this study. The data analysis technique was carried out using software SmartPLS 4.0. The result showed that the Strategic Human Resource Management (SHRM) had positive and significant effect on the job satisfaction in Lembaga Pemasyarakatan Kelas IIA Yogyakarta.